2014
DOI: 10.1007/s00404-013-3141-0
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in the clinical phenotype of adenomyosis and leiomyomas: a retrospective, questionnaire-based study

Abstract: Women with a histologic diagnosis of adenomyosis differ from women who have only leiomyomas at the time of hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
10
2
Order By: Relevance
“…Although several studies have suggested that a history of laparotomy and prior uterine surgery (such as cesarean delivery, myomectomy, dilation and curettage) were related to an increased risk of adenomyosis, we did not find statistically significant differences in terms of the history of previous cesarean delivery and laparotomy between the two groups . Hence, our results did not support the hypothesis that surgically‐induced endometrial implantation may contribute to the development of adenomyosis …”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Although several studies have suggested that a history of laparotomy and prior uterine surgery (such as cesarean delivery, myomectomy, dilation and curettage) were related to an increased risk of adenomyosis, we did not find statistically significant differences in terms of the history of previous cesarean delivery and laparotomy between the two groups . Hence, our results did not support the hypothesis that surgically‐induced endometrial implantation may contribute to the development of adenomyosis …”
Section: Discussioncontrasting
confidence: 94%
“…were related to an increased risk of adenomyosis, we did not find statistically significant differences in terms of the history of previous cesarean delivery and laparotomy between the two groups. 7,18,19 Hence, our results did not support the hypothesis that surgically-induced endometrial implantation may contribute to the development of adenomyosis. 6 The majority of women with myomas are asymptomatic, but abnormal uterine bleeding, pelvic pain and pelvic pressure are the most common symptoms associated with fibroids.…”
Section: Discussioncontrasting
confidence: 94%
“…[83][84][85] The results for menorrhagia and dysmenorrhea have been less consistent when adenomyosis, or adenomyosis with leiomyomas, has been compared with those with pathology-confirmed leiomyomas. 12,43,[86][87][88][89][90][91][92][93] Although in several of these studies, patients with adenomyosis with or without leiomyomas appear to experience a greater frequency of dysmenorrhea than patients with leiomyomas. 12,86,87,90,92 One frequently cited study has suggested that adenomyosis is an incidental finding and not a source of symptoms.…”
Section: Symptomatologymentioning
confidence: 99%
“…In 15% to 57% of cases, uterine leiomyomas and adenomyosis coexist in the same uterus and women with both conditions are more likely to experience pelvic pain 57 . Results from a case-control study on women undergoing hysterectomy showed that women with leiomyoma and adenomyosis were more likely to report dysmenorrhea, dyspareunia, and non-cyclic pelvic pain compared with women with leiomyomas only 3, 57, 58 .…”
Section: Coexistence With Other Gynecological Conditionsmentioning
confidence: 99%